Management of Traumatic Herniation of Buccal Fat Pad in a 22-month-old Child: A Case Report - Sigdel, Bhawana; Shrestha, Sneha; Dali, Mamta; Rai, Amita; Shrestha, Ashish; Koirala, Bandana (Journal of Nepalese Association of Pediatric Dentistry, 2020)
The buccal fat pad is an encapsulated mass located within the buccal facial spaces. It is relatively large in neonate and infants. A tiny perforation on buccal mucosa, fascia or buccinator muscle can lead to the herniation of buccal fat pad in young children. Trauma is the most common etiology. Such situation demands careful examination of oral cavity and thorough history taking to avoid any misdiagnosis. This paper reports a clinical presentation and management of herniation of buccal fat pad on a 22-month-old-girl following trauma to her left cheek region with sugarcane.